The Relationship Between Test Item Format and Gender Achievement Gaps on Math and ELA Tests in Fourth and Eighth Grades. (June 2018) - Reardon, Sean F.; Kalogrides, Demetra; Fahle, Erin M.; Podolsky, Anne; Zárate, Rosalía C.
Prior research suggests that males outperform females, on average, on multiple-choice items compared to their relative performance on constructed-response items. This paper characterizes the extent to which gender achievement gaps on state accountability tests across the United States are associated with those tests' item formats. Using roughly 8 million fourth- and eighth-grade students' scores on state assessments, we estimate state- and district-level math and reading male-female achievement gaps. We find that the estimated gaps are strongly associated with the proportions of the test scores based on multiple-choice and constructed-response questions on state accountability tests, even when controlling for gender achievement gaps as measured by the National Assessment of Educational Progress (NAEP) or Northwest Evaluation Association (NWEA) Measures of Academic Progress (MAP) assessments, which have the same item format across states. We find that test item format explains approximately 25% of the variation in gender achievement gaps among states.